2020
DOI: 10.1039/d0tc02959a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the thermoelectric performance of n-type SnSe: the synergistic effect of NbCl5 doping and dislocation engineering

Abstract: Tin selenide (SnSe) is a promising thermoelectric material because of its advantageous electronic structures and low thermal conductivity. In this work, n-type polycrystalline SnSe0.95 doped by a new dopant NbCl5...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 51 publications
5
27
1
Order By: Relevance
“…[4] We have observed that the intensity of (400) plane is stronger than (111) for all the powdered samples of SnSe 0.92 + x% MoCl 5 indicating the preferential orientation of the crystallites is along [h00] direction. [17,27,29,44] The XRD patterns of SPS'ed SnSe 0.92 + 1% MoCl 5 (x = 0, 1) recorded for both the parallel (||) and perpendicular (⊥) to the SPS direction (see Figure S4, Supporting Information) show a significant change in the relative intensities of (111) and (400) peaks inferring the presence of high degree of anisotropy in the SPS processed samples. We have observed that the relative intensities of (h00) peaks are stronger along the (||) than that along the (⊥) direction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] We have observed that the intensity of (400) plane is stronger than (111) for all the powdered samples of SnSe 0.92 + x% MoCl 5 indicating the preferential orientation of the crystallites is along [h00] direction. [17,27,29,44] The XRD patterns of SPS'ed SnSe 0.92 + 1% MoCl 5 (x = 0, 1) recorded for both the parallel (||) and perpendicular (⊥) to the SPS direction (see Figure S4, Supporting Information) show a significant change in the relative intensities of (111) and (400) peaks inferring the presence of high degree of anisotropy in the SPS processed samples. We have observed that the relative intensities of (h00) peaks are stronger along the (||) than that along the (⊥) direction.…”
Section: Resultsmentioning
confidence: 99%
“…It is the dimensionless thermoelectric figure of merit (zT) that determines the performance of a thermoelectric material and is concentration of polycrystalline SnSe. [22][23][24][25][26][27] Besides, a couple of thermoelectric studies have also shown moderate zT values (far below the zT's of n-type single crystal) in n-type polycrystalline SnSe via Re doping and band-gap engineering. [28,29] As thermoelectric module demands both high performance p-and n-type similar materials, there remains plenty of room to enhance the zT to 2 for the n-type SnSe polycrystals by applying innovative and new strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the AgBiSe 2 addition, the hardness is greatly enhanced by 42% to reach 0.75 ± 0.05 GPa in the x = 0.3 composite. The improvement in hardness may result from two aspects: (i) some Ag + ions enter into the interlayer of BiSbTe and form chemical bonds and (ii) increased impedance against dislocation movements by the emerged defect . As summarized in Figure , the BiSbTe-0.3% AgBiSe 2 sintered composite not only possesses an improved ZT value but also exhibits a higher Vickers hardness than the commercial ZM material.…”
Section: Resultsmentioning
confidence: 99%
“…A plethora of research has focused on enhancing the thermoelectric performance of polycrystalline SnSe, beyond removal of the surface oxide layer. Approaches include controlling carriers by doping with various alkali (Na, K, and Li) and transition metal (Ag, Nb, and Re) cations, hot deformation techniques to promote texturation, alloying with AgSbSe 2 and AgBiSe 2 to promote crystal and electronic structural modulation, and introducing nanofeatures in the SnSe matrix.…”
mentioning
confidence: 99%